State-Centric Approach to Human Rights: Exploring Human Obligations - Mishra, Anumeha (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2019)
The conventional wisdom of rights as a limitation on the power of the State is a product of an archaic understanding that presumed the State is the only entity capable of infringing human rights. With the increased involvement of non-State entities in functions that were erstwhile reserved to the State, we need to re-examine this State-centric approach. The international community is already challenging this State-oriented liberal rights framework. Including individual obligations within the human rights discourse is an outcome of the conflict between the ‘liberal theory of rights’ that emphasizes individual autonomy, and the social democracy theory, that calls for regulating private conduct to strengthen implementation of rights. This article contextualizes the feasibility of including such individual obligations within the human rights discourse, especially in a world where private conduct equally impacts the actualization of rights.